2004
DOI: 10.1523/jneurosci.1413-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Phase Segregation of Medial Septal GABAergic Neurons during Hippocampal Theta Activity

Abstract: Septo-hippocampal GABAergic neurons immunoreactive for parvalbumin are thought to play a crucial role in the generation of hippocampal theta oscillations associated with a specific stage of memory formation. Here we use in vivo juxtacellular recording and filling in the medial septum followed by immunocytochemical identification of the recorded cells containing parvalbumin to determine their firing pattern, phase relationship with hippocampal theta, morphology, and to thereby reveal their involvement in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
285
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(310 citation statements)
references
References 55 publications
23
285
1
Order By: Relevance
“…Inhibitory control of PVϩ interneurons has been suggested to be required for the generation of hippocampal theta rhythm (19,21,22,37). To test this hypothesis we recorded local field potentials (LFP) and unit activity in CA1 stratum pyramidale in behaving PV-⌬␥ 2 and control mice, using wire electrodes during exploration in an open field and sleep in a home cage.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitory control of PVϩ interneurons has been suggested to be required for the generation of hippocampal theta rhythm (19,21,22,37). To test this hypothesis we recorded local field potentials (LFP) and unit activity in CA1 stratum pyramidale in behaving PV-⌬␥ 2 and control mice, using wire electrodes during exploration in an open field and sleep in a home cage.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in this study, we investigated the following possible scenarios: (1) putative pacemaker MS neurons lead hippocampal field theta and hippocampal interneurons, proving a pacemaker role for the MS; (2) the activity changes of hippocampal interneurons precede those of MS cells, supporting the theory of hippocampal pacing of theta; (3) no significant temporal difference can be observed, which raises the possibility of a septal and a hippocampal pacemaker alternating or operating coincidentally, or a potential hidden pacemaker synchronizing the two areas. By implementing the circular statistical Z-shift method (Siapas et al, 2005), we demonstrated that alterations in the activity of the previously identified candidate pacemaker neurons (Borhegyi et al, 2004;Varga et al, 2008) in the MS precede those of putative hippocampal interneurons as well as corresponding changes in hippocampal field theta. Then, by using an information theoretical approach based on mutual information (MI) (Panzeri et al, 2007), we could show that the candidate pacemaker population of PV/HCN neurons share a higher amount of information with hippocampal theta than PV/HCN-immunonegative cells.…”
Section: Introductionmentioning
confidence: 94%
“…Nicotine promotes oscillatory fi eld activity but not rhythmic burst fi ring in the MSDB in vitro The hippocampal theta rhythm in vivo is tied in which the presence of rhythmic burst firing activity recorded by extracellular electrodes in the midline regions of the MSDB [8,26] . Extrinsic, non-cortical inputs to the septum seem to control the incidence of the burst fi ring [7][8][9] , but there has been controversy as to whether this activity in the MSDB is generated intrinsically by tonic input or is driven by theta-patterned input from elsewhere, most notably the SUM [6] .…”
Section: Wwwchinapharcom Lu Cb Et Almentioning
confidence: 99%